Kualitas Spermatozoa Tikus yang Diberi Tepung Kedelai Kaya Isoflavon, Seng (Zn) dan Vitamin E - S Astuti; D Muchtadi; M Astawan; B Purwantara (Faculty of Animal Science, Bogor Agricultural University, 2009)
The objective of this experiment was to evaluate the effects of isoflavone-riched soybean flour, zinc (Zn) and vitamin E on quality of rats spermatozoa as animal model. Diet was given as isonitrogen and isocaloric with 15% of dietary protein. Thirty male Sprague Dawley post weaning rats (21 days old) were divided into six groups and treated with isoflavone-riched soybean flour, Zn and vitamin E in different combination. Isoflavone-riched soybean flour (3 mg/day) was given by oral administration, whereas Zn and vitamin E were mixed with the basic diet. The treatments were given for 2 months. Thirty female Sprague Dawley post weaning rats (21 days old) were used to observe male fertility. Results indicated that synergic interaction between isoflavone-riched soybean flour, Zn and vitamin E increased motility and concentration of rats spermatozoa. The treatment was not significant on relative weight of testis, conception rate and foetus size. The best results was shown by the group which was given isoflavone-riched soybean flour with diet containing both Zn and vitamin E, i.e. motility rate of 79.50±1.12%, sperm concentration of 1636.90±87.95 million/ml, and abnormality rate of 9.00±0.70%. Conception rate and the number of foetus on female rats were 100% and 11±0.71, respectively. It is concluded that combination treatment of isoflavone-riched soybean flour, Zn and vitamin E on male rats showed the best fertility in comparison with single treatment and the other combination. Key words: isoflavone-riched soybean, Zn, vitamin E, quality of spermatozoa, rat